Recent progress in drug delivery of pluronic P123: pharmaceutical perspectives. (3rd July 2017) - Zhao, Li-Yan; Zhang, Wan-Ming
Abstract: This review focuses on recent investigations that used Pluronic P123 (P123) as pharmaceutical ingredients in vesicle, micelle, mixed micelle, in situ gel, tablet and emulsion. The main results from these studies show that P123 can significantly increase the stability of incorporated hydrophobic drugs with enhanced in vitro cytotoxicity and cellular uptake of anticancer drugs. Moreover, modified forms of P123 with RGD, folate or other targeted marker have shown its therapeutic potentials in various types of tumors and cancers. Furthermore, modified forms of P123 alone and/or mixed with other copolymers have less toxic effects and more tumor-specific delivery of anticancer drugs. They are promising materials as a nanoplatform for the drug delivery. Finally, the future perspectives of the field are briefly discussed.